Evaluating changes in the monetary transmission mechanism in the Czech Republic - Michal Franta; Roman Horváth; Marek Rusnák (Charles University in Prague, Institute of Economic Studies (IES), 2012)
We investigate the evolution of the monetary policy transmission mechanism in the Czech Republic over the 1996-2010 period by employing a time-varying parameters Bayesian vector autoregression model with stochastic volatility. We evaluate whether the response of GDP and the price level to exchange rate or interest rate shocks changes over time, with a focus on the period of the recent financial crisis. Furthermore, we augment the estimated system with a lending rate and credit growth to shed light on the relative importance of financial shocks for the macroeconomic environment. Our results suggest that output and prices have become increasingly responsive to monetary policy shocks, probably reflecting financial sector deepening, more persistent monetary policy shocks, and overall economic development associated with disinflation. On the other hand, exchange rate pass-through has weakened somewhat over time, suggesting improved credibility of inflation targeting in the Czech Republic with anchored inflation expectations. We find that credit shocks had a more sizeable impact on output and prices during the period of bank restructuring with difficult access to credit. In general, our results show that financial shocks are less important for the aggregate economy in an environment of a stable financial system.
Keywords: E44; E52; 330; Monetary policy transmission; Sign restrictions; Time-varying parameters